-2(j+5)+6=4(j+2)

Simple and best practice solution for -2(j+5)+6=4(j+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(j+5)+6=4(j+2) equation:


Simplifying
-2(j + 5) + 6 = 4(j + 2)

Reorder the terms:
-2(5 + j) + 6 = 4(j + 2)
(5 * -2 + j * -2) + 6 = 4(j + 2)
(-10 + -2j) + 6 = 4(j + 2)

Reorder the terms:
-10 + 6 + -2j = 4(j + 2)

Combine like terms: -10 + 6 = -4
-4 + -2j = 4(j + 2)

Reorder the terms:
-4 + -2j = 4(2 + j)
-4 + -2j = (2 * 4 + j * 4)
-4 + -2j = (8 + 4j)

Solving
-4 + -2j = 8 + 4j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-4j' to each side of the equation.
-4 + -2j + -4j = 8 + 4j + -4j

Combine like terms: -2j + -4j = -6j
-4 + -6j = 8 + 4j + -4j

Combine like terms: 4j + -4j = 0
-4 + -6j = 8 + 0
-4 + -6j = 8

Add '4' to each side of the equation.
-4 + 4 + -6j = 8 + 4

Combine like terms: -4 + 4 = 0
0 + -6j = 8 + 4
-6j = 8 + 4

Combine like terms: 8 + 4 = 12
-6j = 12

Divide each side by '-6'.
j = -2

Simplifying
j = -2

See similar equations:

| -4r-2r-6-4= | | -3-(-17)=-4 | | f(x)=8x-x^2 | | 1k-8=-10 | | 17x+2=25x-3 | | 1.5+x=7 | | 3.75c+1.125=10.25 | | 4(3z+12)-11=12z+37 | | 2x+9-.74x+2.24= | | 5(2x-1)-9= | | 5(2x-3)=21+4x | | 6m=2n+r | | 8x+3=180 | | x=-2.1538 | | -12+8m=-2m+48 | | 8-3(2x-1)=4(3-2x) | | 7/6-a-4/9=-a | | 15+17y=14+9y | | 8-.67x=72 | | X+8y=10 | | (2x+6)+(2x-6)+x=180 | | 8+7x=12+5x | | -4y-0=8 | | 9x-y=40 | | 2(m-7)+4m=7m+8-m | | x*2=8.3 | | 8=4x-(6x-2) | | 9n+-10+20n-20n=11 | | -1.7j-4.8=2 | | y=.75(12) | | x^2=8.2 | | 4x^7-28x+20x^5= |

Equations solver categories